2022
DOI: 10.3390/jcm11082133
|View full text |Cite
|
Sign up to set email alerts
|

Orthodromic and Antidromic Snare Techniques for Left Ventricular Lead Implantation in Cardiac Resynchronization Therapy

Abstract: The snare technique can be used to overcome unsuitable cardiac venous anatomies for left ventricular (LV) lead implantation in cardiac resynchronization therapy (CRT) procedures. However, limited data exist regarding performance of the snare technique. We classified 262 patients undergoing CRT procedure into the snare (n = 20) or conventional group (n = 242) according to the LV lead implantation method. We compared the safety, efficacy, and composite outcome (all-cause death and heart failure readmission) at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, Kim et al reported that vessel perforation, pericardial effusion, cardiac tamponade, and lead damage did not occur when the snare technique was used. 6 When the snare technique cannot be performed due to a lack of connecting vessels, epicardial lead implantation, or conduction system pacing could be alternative options. 11 , 12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Kim et al reported that vessel perforation, pericardial effusion, cardiac tamponade, and lead damage did not occur when the snare technique was used. 6 When the snare technique cannot be performed due to a lack of connecting vessels, epicardial lead implantation, or conduction system pacing could be alternative options. 11 , 12 …”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 The anti-dromic snare technique for CS lead implantation was reportedly very useful when the target vessel was dissected, stenotic, or tortuous. 6 , 7 Herein we present a case of re-implantation of a CS lead using the anti-dromic snare technique into the occluded vessel after CS lead extraction.…”
Section: Introductionmentioning
confidence: 99%
“…More simple to use would be QRS narrowing by CRT [37]; however, super-response can occur in the absence of a significant reduction in QRS duration. Reaching an optimal lead position can be difficult, but improved technologies such as snare techniques have increased the number of target veins within the coronary sinus [38].…”
mentioning
confidence: 99%